Liang Teh Pontianak Kaya Antioksidan Pada Berbagai Formulasi Substitusi Massa Rasio Jahe Gamprit - Ramadhani, Amoria S; Dewi, Yohana S K; Saputri, Nur E (Universitas Pattimura, 2024)
Liang Tea Pontianak (LTP) is a rich antioxidant herbal tea composed of a mixture of several plant ingredients, including muje leaves (Dicliptera chinensis), oregano leaves (Origanum vulgare), pineapple shell leaves (Tradescantia spathacea), pandan leaves (Pandanus amaryllifolius), and aloe vera (Aloe vera chinensis). Adding ginger to Liang Tea Pontianak has not been explored, but the ginger mixture has an innovative, antioxidant-rich flavor in LTP. This research aimed to obtain the mass ratio of ginger substitution in the formulation that produces the best sensory and physicochemical characteristics of antioxidant-rich LTP. This study employed a Randomized Group Design with a single factor, comprising five treatment levels of ginger mass ratio substitution in LTP ((2:0), (1.9:0.1), (1.8:0.2), (1.7:0.3), and (1.6:0.4)) with five replications. The results showed that the best sensory and physicochemical characteristics of Liang Tea Pontianak with ginger substitution were obtained in the treatment of 1.8:0.2, which exhibited the best sensory test values for color 4,24 ± 0,83 (more liked), aroma 3.76 ± 0,97 (liked), and taste 3.56 ± 0,92 (liked). The physicochemical analysis yielded the following values: L* color (31.90 ± 2,08), a* color (3.20 ± 0,81), b* color (5.70 ± 0,53), total flavonoids 82.71 ± 6,16 mg QE/g, and antioxidant activity 78.90 ± 4,40%.